Державні видатки в епоху цифрових технологій - Синютка, Н. Г.; Курило, О. Б.; Synyutka, N.; Kurylo, O. (Видавництво Львівської політехніки, 2019)
На основі аналізу наукових публікацій визначено базові підходи до розуміння публічного споживання та системи державних закупівель. Закономірно, що глобальна автоматизація та оцифрування фінансових процесів вимагає якісних змін і у політиці державних видатків. Детерміновано основні напрями впливу інноваційної цифрової парадигми на прозорість та ефективність державних видатків. Значну увагу приділено запровадженню системи електронних публічних закупівель ProZorro. Обґрунтовано доцільність її імплементації у вітчизняну практику бюджетних видатків, проаналізовано принципи та процедури впровадження. Узагальнено динаміку публічних закупівель в Україні. Зроблено висновки про переваги електронної системи, серед яких: прозорість та неупередженість, стимулювання конкуренції та недискримінація учасників торгів, зниження корупції, ефект масштабування економії бюджетних коштів задля зростання суспільного добробуту. Наголошено на потенційних ризиках, загрозах та недоліках системи ProZorro.

The aim of the article is to study transformation of public expenditures in the context of a global trend of the digital economy development and the information society formation. Based on the analysis of scientific publications, the fundamental approaches to understanding public consumption and the system of state purchases have been determined. Obviously, global automation and digitalization of financial processes require significant changes in the public spending policy. The main effects of innovative digital paradigm on transparency and efficiency of state expenditures are determined. Considerable attention is paid to the introduction of electronic public procurement system ProZorro. The expediency of its implementation in national practice of budget expenditures is substantiated, the principles and procedures of implementation are analyzed. The dynamics of public procurement in Ukraine is summarized. The conclusions on the advantages of electronic system are made, including transparency and impartiality, stimulation of competition and non-discrimination of bidding participants, reduction of corruption, the effect of reducing the savings of budget funds for the growth of public welfare. The potential risks, threats and shortcomings of the ProZorro system are highlighted.
Public spending in the era of digital technology
Keywords: державні послуги; державні видатки; фіскальний простір; діджиталізація; публічні закупівлі; ProZorro; public services; public spending; fiscal space; digitalization; public procurement; ProZorro; 336.5.02